HUBUNGAN PANJANG TUNGKAI DENGAN KEMAMPUAN LOMPAT JAUH GAYA JONGKOK MAHASISWA PENDIDIKAN JASMANI KESEHATAN DAN REKREASI ANGKATAN 2018 UHO - Nur Aeni; Muhammad Rusli; La Ode Rusdin (Universitas Halu Oleo, 2021)
The purpose of this study was to determine how much the relationship between leg length and squat style long jump ability in students of the physical education department / study program health and recreation, class 2018. The population in this study were all students of Physical Education for Health and Recreation, batch 2018, amounting to 88 people consisting of 73 boys and 15 girls, the sample in this study was taken by purposive sampling, which is then based on the skills to make good jumps, right and right. So that it is obtained 35 students as a sample. The instrument used to measure the length of the limbs was the Anthropometer, while to measure the long jump ability of the squatting force was the squat-style long jump test. The data in this study were analyzed using the product moment statistical technique 0.05%. In the study it was concluded that there was a relationship between leg length and the ability to jump long jump squatting where rxy = 0.49> r table 0.334. while the coefficient of determination (r ^ 2) = 0.24 or 24%. This shows that the level of correlation between the leg length variable (X) and the squat style long jump ability (Y) is in moderate correlation. Besides, 76% is influenced by other biomechanical factors. The results of this study indicate that leg length has a significant relationship with the squat style long jump ability of students of the Health and Recreation Physical Education Department / study program, batch 2018.